Stone Enclosures —Linking Time and Guiding Space - Kerstin Cassel (Current Swedish Archaeology, 1996)
From the late Roman Iron Age, stone enclosures and houses with a stone foundation have been built on Gotland. Stone enclosures have generally been interpreted as fences between the infields and the outlying land. I will argue that this explanation is insufficient and that we also have to consider the enclosures' symbolic and social significance. The stone enclosures were part of people's everyday practice as they moved through the landscape, and the enclosures structured the reality. The stone enclosures can be seen as both linking and separating, and one interpretation put forward is that the enclosures "embody" the social structure.